Regulation of CD45 phosphatase by oncogenic ALK in anaplastic large cell lymphoma - Mura, Giulia; Karaca Atabay, Elif; Menotti, Matteo; Martinengo, Cinzia; Ambrogio, Chiara; Giacomello, Gloria; Arigoni, Maddalena; Olivero, Martina; Calogero, Raffaele A.; Chiarle, Roberto; Voena, Claudia (Frontiers in Oncology, 2023)
Anaplastic Large Cell Lymphoma (ALCL) is a subtype of non-Hodgkin lymphoma frequently driven by the chimeric tyrosine kinase NPM-ALK, generated by the t (2,5)(p23;q35) translocation. While ALK+ ALCL belongs to mature T cell lymphomas, loss of T cell identity is observed in the majority of ALCL secondary to a transcriptional and epigenetic repressive program induced by oncogenic NPM-ALK. While inhibiting the expression of T cell molecules, NPM-ALK activates surrogate TCR signaling by directly inducing pathways downstream the TCR. CD45 is a tyrosine phosphatase that plays a central role in T cell activation by controlling the TCR signaling and regulating the cytokine responses through the JAK/STAT pathway and exists in different isoforms depending on the stage of T-cell maturation, activation and differentiation. ALK+ ALCL cells mainly express the isoform CD45RO in keeping with their mature/memory T cell phenotype. Because of its regulatory effect on the JAK/STAT pathway that is essential for ALK+ ALCL, we investigated whether CD45 expression was affected by oncogenic ALK. We found that most ALK+ ALCL cell lines express the CD45RO isoform with modest CD45RA expression and that NPM-ALK regulated the expression of these CD45 isoforms. Regulation of CD45 expression was dependent on ALK kinase activity as CD45RO expression was increased when NPM-ALK kinase activity was inhibited by treatment with ALK tyrosine kinase inhibitors (TKIs). Silencing ALK expression through shRNA or degradation of ALK by the PROTAC TL13-112 caused upregulation of CD45RO both at mRNA and protein levels with minimal changes on CD45RA, overall indicating that oncogenic ALK downregulates the expression of CD45. CD45 repression was mediated by STAT3 as demonstrated by ChIP-seq data on ALCL cells treated with the ALK-TKI crizotinib or cells treated with a STAT3 degrader. Next, we found that knocking-out CD45 with the CRISPR/Cas9 system resulted in increased resistance to ALK TKI treatment and CD45 was down-regulated in ALCL cells that developed resistance in vitro to ALK TKIs. Overall, these data suggest that CD45 expression is regulated by ALK via STAT3 and acts as a rheostat of ALK oncogenic signaling and resistance to TKI treatment in ALCL.